The interplay of food-related lifestyle and eating behavior in Italian women - Hamam, Manal; D’Amico, Mario; Spina, Daniela; La Via, Giovanni; Di Vita, Giuseppe (Frontiers in Nutrition, 2024)
Women played a crucial role in food shopping and preparation and their food choices have important implications for their health and that of their families. This study aims to provide a perspective on women's eating lifestyle, which has undergone significant changes. A factor analysis were conducted to assess the degree of involvement in food choices and the type of food items consumed among a sample of 399 Italian women. Through cluster analysis, four segments were identified: hedonic food consumers; sustainable-and balanced-diet consumers; food experimenters; and no food fondness consumers. The results reveal a correlation between the degree of food involvement and the type of food consumed. Furthermore, the food lifestyle of the sample is partially dependent on age. Individuals aged 25-28 years show more hedonic food consumption behavior, while the older age group (44-64 years) fall into the sustainable and balanced diet consumer cluster (the largest cluster) and the cluster of those who do not express definable food choices (no food fondness).